Pengembangan Sikap Keberagamaan Remaja melalui Pendidikan Sufistik - Ossi Marga Ramadhan; Opik Taufik Kurahman; Supiana Supiana; Hisny Fajrussalam (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2021)
This study aims to determine the offer and integration of Sufistic education on adolescent religious attitudes. This research uses a descriptive qualitative approach with the type of library research. Researchers obtain data from various literature such as books, journals, scientific works, and other documents that examine research-related themes. The data obtained is then analyzed by first reducing the data, presenting the data, and drawing conclusions. The results found that Sufistic education can be reviewed and integrated into aspects of adolescent attitude formation (cognitive, affective, conative) by studying Shari'a education with the aim of Sufism in the cognitive aspect, through a psychological-humanist approach in the affective aspect, and through tafakkur activities to perfect the conative aspect. The creation of these three aspects must be supported by religious disciplines in their environments, such as character and role models from teachers and parents, instilling a sense of faith in adolescents, and a good religious environment.